Substrate‐directed diastereoselective hydroformylation: key step for the assembly of polypropionate subunits - Breit, Bernhard; Dauber, Mario; Harms, Klaus (Chemistry - a European journal, 1999)
Abstract o-DPPB-Directed hydroformylation could serve as a key step for the construction of bifunctionalized stereotriad building blocks, which form the basis of polyketide natural products (see scheme). The prepared building blocks are well suited to permit polyketide chain extensions into both directions of the main chain. o-DPPB=ortho-diphenylphosphanylbenzoyl.
Gesehen am 21.03.2018